2013
DOI: 10.1111/cch.12073
|View full text |Cite
|
Sign up to set email alerts
|

Developing web‐based Triple PPositive Parenting Programme’ for families of children with asthma

Abstract: Although parents of children with asthma show willingness to access web-based parenting support, further work is necessary to develop engaging websites and determine barriers to uptake, and adherence to online parenting interventions with this population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
0
21
0
Order By: Relevance
“…Although the relatively smaller size of the asthma sub-sample may have limited our ability to detect significant effects, particularly in the case of parents' asthma management self-efficacy, the effect sizes for the asthma-specific child behaviour extent and confidence were nevertheless much smaller compared to those for eczema (Tables 3 and 2, respectively). Equivocal results have previously been reported for parenting intervention in the context of asthma (Clarke et al, 2014). In this study, at baseline parents had more confidence with managing asthma behaviours than eczema behaviours, leaving less room for improvement.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Although the relatively smaller size of the asthma sub-sample may have limited our ability to detect significant effects, particularly in the case of parents' asthma management self-efficacy, the effect sizes for the asthma-specific child behaviour extent and confidence were nevertheless much smaller compared to those for eczema (Tables 3 and 2, respectively). Equivocal results have previously been reported for parenting intervention in the context of asthma (Clarke et al, 2014). In this study, at baseline parents had more confidence with managing asthma behaviours than eczema behaviours, leaving less room for improvement.…”
Section: Discussionmentioning
confidence: 56%
“…Behavioural parenting interventions are recognised as best practice in the treatment of parenting and child behaviour difficulties (O'Connell, Boat, & Warner, 2009), however these have rarely been applied in the context of child illness management (Kirk et al, 2012). Recent studies have demonstrated some positive, albeit mixed, effects of parenting intervention for child chronic conditions (Clarke, Calam, Morawska, & Sanders, 2014;Doherty, Calam, & Sanders, 2013;Lohan, Morawska, & Mitchell, 2015;Sassmann, de Hair, Danne, & Lange, 2012;Westrupp, Northam, Lee, Scratch, & Cameron, 2015) providing promising signs that this approach may add value to existing health services.…”
Section: Introductionmentioning
confidence: 99%
“…These programs aim to encourage parents to use more positive and effective educational practices and to teach them how to coach their chronically ill child to control pain or other symptoms. Several family-based CBT programs to control chronic pain, which include multiple elements, such as relaxation training, activity pacing, problem solving, and distraction techniques (Nieto et al, 2015;Palermo et al, 2016Palermo et al, , 2009Stinson et al, 2010) have offered preliminary evidence Other examples are the Triple-P programs for parents of children with asthma (Clarke et al, 2013) and type-1 diabetes (Doherty et al, 2013). These programs, derived from the Triple P Positive Parenting Program to prevent behavioural and emotional child problems, are based on the social learning theory and are aimed at increasing parental self-efficacy, through training on disease management strategies.…”
Section: Psychological Methods Involvedmentioning
confidence: 99%
“…Task completion is followed by individually tailored feedback on progress, incentives, and reinforcement or suggestions to overcome difficulties. Most online programs are theory-driven interventions, and replicate face-to-face programs that have been previously empirically validated (Clarke, Calam, Estudos de Psicologia I Campinas I 34(3) I 331-344 I julho -setembro 2017 Morawska, & Sanders, 2013;Doherty, Calam, & Sanders, 2013). In some cases, the technologymediated programs are delivered combined with face-to-face sessions (e.g., Maddison et al, 2014).…”
Section: Technologies Usedmentioning
confidence: 99%
“…Given the service domain in health care, the issue of accessibility is all the more important, and much discussion has been held on issues of access to services [24,25]. The accessibility score is an assessment of a website’s ease of use for individuals with lower computer literacy levels, including those with physical disabilities that limit their use of a mouse or non-standard browser (such as mobile phones or tablet devices).…”
Section: Methodsmentioning
confidence: 99%